THE SIGNIFICANCE OF MEDIA LINGUISTICS IN THE LANGUAGE OF MODERN MASS MEDIA - Teshabaeva Dilfuza (Web of Journals Publishing, 2024)
A new area of linguistics has been dedicated to the study of media text. The study of media speech and mass communication language is known as medialinguistics. Language imperialism and the English-speaking influence on international media are topics of discussion in contemporary foreign studies. Ideologically-modal vocabulary plays a significant influence in the stylistic features of media speech as it relates to the expression of opinion and evaluation in informational and analytical texts. This influence is examined in the article using the Uzbek media as an example.
Keywords: media linguistics, mass media language, mass communication, world view, linguistic imperialism.